2015
DOI: 10.1080/00036846.2015.1039701
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of current account deficits in India: an intertemporal perspective

Abstract: This study examines the sustainability of current account deficits (CADs) and the validity of intertemporal budget constraint (IBC) in India. The long-run model is estimated on annual data for the period 1950-1951 to 2009-2010. The optimal single-equation and maximum-likelihood (ML) system estimates of the model provide a consistent support for the longrun relationship between imports and exports. The OLSGH estimates provide no support and that ML system estimates a consistent support for cointegration in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
2
9
0
1
Order By: Relevance
“…The results revealed the difference in the adjustments of current account sustainability followed by positive and negative shocks. Singh (2015) used an optimal single-equation system and maximum-likelihood method as an estimator. The obtained estimates on annual data for the period of 1950-2010 provided empirical evidence to support the existence of a long-run relationship between imports and exports in India.…”
Section: Theoretical Background and Brief Related Literature Overviewmentioning
confidence: 99%
“…The results revealed the difference in the adjustments of current account sustainability followed by positive and negative shocks. Singh (2015) used an optimal single-equation system and maximum-likelihood method as an estimator. The obtained estimates on annual data for the period of 1950-2010 provided empirical evidence to support the existence of a long-run relationship between imports and exports in India.…”
Section: Theoretical Background and Brief Related Literature Overviewmentioning
confidence: 99%
“…Murat et al (2014) found the same as the previous study. Singh (2015) pointed out that India satisfied the constraint for the long length sample. Dugler (2016) presented the results which indicate that for all countries the stability tests reject the null of coefficient stability of the long-run relationship between exports and imports, and that cointegration tests imply weak form of sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Husted (1992) built the intertemporal solvency condition for a nation on the basis of a mean reverting current account imbalances and a long-run equilibrium relationship between exports and imports. Several studies examine the solvency test by assessing the cointegration relationships between exports and imports of developed nations (see, Leachman and Thorpe 1998;Liu and Tanner 1996;Önel and Utkulu 2006;Singh 2019;Wickens and Uctum 1993); and emerging and transition nations (see, Hassan et al (2016) for Middle East and African (MEA) countries; Wadud et al (2015) for Bangladesh; Singh (2015) for India; Gnimassoun and Coulibaly (2014) for Sub-Saharan Africa; Holmes et al (2011) for India; Greenidge et al (2011) for Barbados; Pattichis (2010) for Cyprus; Yol (2009) for Tunisia and Egypt and for Morocco; Ismail and Baharumshah (2008) for Malaysia; for 22 least developed countries; Narayan and Narayan (2004) for Fiji and Papua New Guinea; and Baharumshah et al (2003) for four ASEAN nations).…”
Section: Introductionmentioning
confidence: 99%
“…We found that only a few studies allow for structural breaks for solvency tests (see Baharumshah et al (2003) for four ASEAN countries; Önel and Utkulu (2006) for Turkey, Singh (2015) for India; Singh (2019) for OECD countries). Singh (2019), which is one of the latest studies, tested the solvency condition with data leading up to 2006, and found support for current account sustainability in the presence of structural breaks.…”
Section: Introductionmentioning
confidence: 99%